Assessment of long term ecotoxicity of urban stormwaters using a multigenerational bioassay on Ceriodaphnia dubia: A preliminary study. Issue 3 (23rd February 2018) - Gosset, Antoine; Wigh, Adriana; Bony, Sylvie; Devaux, Alain; Bayard, Rémy; Durrieu, Claude; Brocart, Melissa; Applagnat, Marine; Bazin, Christine
ABSTRACT: Standardized ecotoxicity bioassays show some limits to assess properly long-term residual toxicity of complex mixture of pollutants often present at low concentration, such as stormwaters. Among invertebrate organisms used for ecotoxicity testing, the microcrustacean Ceriodaphnia dubia ( C. dubia ) is considered as one of the most sensitive, especially regarding reproduction impairment as a toxicity endpoint. Consequently, this work explores the interest to perform a multigenerational assay based on the study of the reproduction of C. dubia to assess long-term ecotoxicity of complex mixture, using stormwater samples. With this in mind, a battery of standardized bioassays ( Daphnia magna mobility, Pseudokirchneriella subcapitata population growth, Heterocypris incongruens growth and one generation C. dubia reproduction inhibition assays) was performed in parallel to a three generation C. dubia reproduction inhibition assay on 2 stormwater samples. Results highlighted that while all standardized bioassays failed to reveal residual toxicity in the stormwater samples, the C. dubia multigenerational assay exhibited an higher sensitivity than the previous ones. No adverse effect was observed for the first exposed generation, but an increase in mortality and a reproduction disturbance was obtained in the second and third exposed generation depending of the sample. Further experiments are now needed to optimize the exposure protocol of this multigenerational assay.